Global warming coverage in the media: trends in a Mexico City newspaper - Deines, Tina (Kansas State University, 2007)
Global warming and its implications have astounding consequences for the global community. Although some research has been done on the trends within environmental reporting, few studies have looked at the issue of global warming in particular. Global warming is a troublesome issue for reporters for a number of reasons, and hence, it is important that we delve into how newspapers cover the topic. Latin America, especially the Caribbean region, is expected to suffer extreme consequences due to global warming, yet no studies regarding global warming coverage have been done in these regions. The first purpose of this study was to discover how a Mexico newspaper frames the issue of global warming. Next, this study sought to expand the current knowledge of global warming coverage by the media. Lastly, this study sought to expand on existing literature to discover how journalists outside of the United States communicate, to the public, the issue of global warming. Based on previous studies on global warming a frame analysis was conducted to explore how the Mexico City-based newspaper Reforma covers the issue of global warming. This study identified that ecology/science and consequences are the most frequently occurring themes of coverage, while scientific conflict and North/South conflict are present, but in low frequencies and near the end of stories. This study also identified international relations as the most frequent solution to global warming, while global warming story frequencies peaked during international conferences. These results confirm previous research, which has found that news media outside of the United States tend to emphasize international relations and de-emphasize conflicts and controversies.
Keywords: Mexico; global warming; climate change; media framing; Latin America; news frames; Environmental Sciences (0768); Journalism (0391); Mass Communications (0708)